Penerapan Data Mining Untuk Prediksi Jumlah Total Porduksi Bakpao Pada PT. Estetika Tata Tiara Menggunakan Algoritma Regresi Linier Berganda - Wicaksana, Prasetya; Pakereng, Magdalena A. Ineke (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Production objective planning is the process of identifying the product to be produced, the required quantity, the completion deadline, and what sources will be needed. The research objective is to determine the total production of Bakpao PT. Estetika Tata Tiara uses multiple linear regression algorithm. At this stage, the data mining technique uses multiple linear regression algorithms. This research was conducted at PT. Aesthetics of Tata Tiara which is a bakpao production company. The results show that the regression equation obtained from the results of multiple linear regression analysis is for the prediction of Bakpao in April 2022 as follows: Y = 473.531 + 0.56 X1 + 0.043 X2. After the analysis, it can be concluded that the variables X1 and X1 affect the prediction of the amount of Bakpao production in 2022. The relationship between sales (X1) and stock (X2), and Bakpao production has a strong positive and unidirectional relationship.